Emotional intelligence : managing emotions to make a positive impact on your life and career - Hasson, Gill (Capstone, 2014)
Emotional Intelligence is fast becoming the skill to master that will unlock your true potential. You have probably noticed that it's not the smartest people that are the most successful or the most fulfilled in life; being clever, talented or skilled is not enough. It's your ability to manage your feelings, other people and your interactions with them that makes the difference. We're all born with this ability emotional intelligence is a skill and we all have the capacity to develop this skill. This book will show you how. It will change the way you think about emotions. Instead of thinking of emotions as being positive or negative, you will learn that all emotions have a positive intent all emotions have our best interests in mind. Improve your emotional intelligence and you improve your ability to understand and manage emotions. You can think clearly and creatively, manage stress and challenges, communicate well with others and display trust, empathy and confidence. You will be in a better position to handle situations, events and other people that in the past you've found difficult or stressful. Emotional Intelligence will show you how to heighten your EQ and improve your personal and work life, including how to be more assertive and confident express how you feel, what you want and don't want. understand what others are feeling and forge stronger relationships manage office politics and navigate the social complexities of the workplace manage anxiety, anger and disappointment deal with bullying motivate and inspire others